2013
DOI: 10.1128/jcm.00744-13
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Calibrator Material for Nucleic Acid-Based Assays for Diagnosing Aspergillosis

Abstract: Twelve laboratories evaluated candidate material for an Aspergillus DNA calibrator. The DNA material was quantified using limiting-dilution analysis; the mean concentration was determined to be 1.73 × 10 10 units/ml. The calibrator can be used to standardize aspergillosis diagnostic assays which detect and/or quantify nucleic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Finally, based on the findings of the aforementioned studies, the Aspergillus Technology Consortium created and validated an Aspergillus sp. DNA calibrator material that can be used to standardize nucleic acid-based diagnostic assays, thus improving interlaboratory comparisons of qualitative and quantitative results between different techniques (184). Although the repercussions of these endeavors have yet to be realized in ensuing clinical trials, it is anticipated that they will reduce the inconsistencies observed in previous studies and will pave the way to large-scale implementation of Aspergillus sp.…”
Section: Pcrmentioning
confidence: 99%
“…Finally, based on the findings of the aforementioned studies, the Aspergillus Technology Consortium created and validated an Aspergillus sp. DNA calibrator material that can be used to standardize nucleic acid-based diagnostic assays, thus improving interlaboratory comparisons of qualitative and quantitative results between different techniques (184). Although the repercussions of these endeavors have yet to be realized in ensuing clinical trials, it is anticipated that they will reduce the inconsistencies observed in previous studies and will pave the way to large-scale implementation of Aspergillus sp.…”
Section: Pcrmentioning
confidence: 99%
“…In an attempt to address qPCR assay variability, the EAPCRI collaborated with the Aspergillus Technology Consortium (AsTeC) and Invasive Aspergillosis Animal Models (IAAM) group to create an A. fumigatus DNA calibrator (49). Twelve clinical and research laboratories in the United States and Europe independently determined the concentration of DNA in the calibrator by performing replicate testing of a dilution series.…”
Section: Molecular Methods For Direct Detection Of Aspergillus In CLImentioning
confidence: 99%
“…Specific to mycology, the European Aspergillus PCR initiative (EAPCRI) has offered recommendations to provide optimal methodology when testing whole-blood and serum samples by Aspergillus PCR (5,6). An international standard has been developed, providing reference material for assay comparison and validation (7).…”
mentioning
confidence: 99%